TERAPI PEMAAFAN UNTUK MENINGKATKAN SUBJECTIVE WELL-BEING PADA ISTRI YANG MENGALAMI KEKERASAN DALAM RUMAH TANGGA - Pratiwi, Yasintha Sari (Jurnal Bimbingan dan Konseling Borneo, 2022)
The background of this research is that a wife has experienced domestic violence and finds it difficult to accept the experience of domestic violence. The purpose of this research is to increase SWB in wives who have experienced domestic violence by giving forgiveness therapy. The type of research is action research single case experimental design with two subjects. Data collection techniques used interview observations and the SWB scale which consisted of life satisfaction and positive negative affect components. The method of data analysis was carried out by means of qualitative quantitative analysis. Quantitative analysis used Kendalls'Wa non-parametric statistical tests, while qualitative analysis was carried out based on written documents summarized during the assessment process to follow-up. The quantitative results showed that the P value of life satisfaction = 0.263 (p 0.05), the positive P affect = 0.105 (p 0.05) and the negative P affect = 0.115 (p 0.05) indicating that the quantitative hypothesis test did not there is a significant increase in SWB. Meanwhile, based on the results of the qualitative analysis, it was concluded that in general, forgiveness therapy can increase SWB in wives who experience domestic violence because they feel the benefits and changes from each stage of the intervention.Keywords : wife has experienced domestic violence (KDRT), SWB, Forgiveness therapy